The Significance of Financial Transactions in the Process of Proving Economic Crimes and Money Laundering - Ismawanto Somantri (PT. AVID MEDIA INDONESIA, 2026)
Financial transactions play a crucial role in the process of proving economic crimes and money laundering, as they are the primary means of tracing the flow of proceeds of crime (follow the money). This study aims to analyze the significance of financial transactions as evidence, the forms and patterns of transactions used to disguise the proceeds of crime, and the authority of law enforcement agencies in utilizing financial transaction data for evidentiary purposes. The method used is normative legal research through library research and qualitative analysis of relevant laws, doctrines, and literature. The results indicate that financial transactions play a significant role in proving economic crimes and money laundering. The complex and evolving transaction patterns that follow the stages of money laundering (placement, layering, integration) require in-depth analysis. Law enforcement agencies, including the Police, the Prosecutor's Office, and the Corruption Eradication Commission (KPK), utilize financial transaction data from the Financial Transaction Reports (PPATK), such as the Suspicious Financial Transaction Report (LTKM), as primary evidence. This suspicious transaction reporting and analysis system enables effective tracing of the flow of proceeds of crime to support investigations, inquiries, and evidence presentation in court